Altered metabotropic glutamate receptor 5 markers in PTSD: In vivo and postmortem evidence - Holmes, Sophie E.; Girgenti, Matthew J.; Davis, Margaret T.; Pietrzak, Robert H.; DellaGioia, Nicole; Nabulsi, Nabeel; Matuskey, David; Southwick, Steven; Duman, Ronald S.; Carson, Richard E.; Krystal, John H.; Esterlis, Irina (Proceedings of the National Academy of Sciences - PNAS, 2017)
Posttraumatic stress disorder (PTSD) is a prevalent and highly disabling disorder, but there is currently no targeted pharmacological treatment for it. Dysfunction of the glutamate system has been implicated in trauma and stress psychopathology, resulting in a growing interest in modulation of the glutamate system for the treatment of PTSD. Specifically, the metabotropic glutamate receptor 5 (mGluR5) represents a promising treatment target. We used [18F]FPEB, a radioligand that binds to the mGluR5, and positron emission tomography (PET) to quantify in vivo mGluR5 availability in human PTSD vs. healthy control (HCs) subjects. In an independent sample of human postmortem tissue, we investigated expression of proteins that have a functional relationship with mGluR5 and glucocorticoids in PTSD. We observed significantly higher cortical mGluR5 availability in PTSD in vivo and positive correlations between mGluR5 availability and avoidance symptoms. In the postmortem sample, we observed up-regulation of SHANK1, a protein that anchors mGluR5 to the cell surface, as well as decreased expression of FKBP5, implicating aberrant glucocorticoid functioning in PTSD. Results of this study provide insight into molecular mechanisms underlying PTSD and suggest that mGluR5 may be a promising target for mechanism-based treatments aimed at mitigating this disorder.